Migration of implanted markers for image‐guided lung tumor stereotactic ablative radiotherapy. (4th March 2013) - Hong, Julian C.; Eclov, Neville C.W.; Yu, Yao; Rao, Aarti K.; Dieterich, Sonja; Le, Quynh‐Thu; Diehn, Maximilian; Sze, Daniel Y.; Loo, Billy W.; Kothary, Nishita; Maxim, Peter G.
Abstract : The purpose of this study was to quantify postimplantation migration of percutaneously implanted cylindrical gold seeds ("seeds") and platinum endovascular embolization coils ("coils") for tumor tracking in pulmonary stereotactic ablative radiotherapy (SABR). We retrospectively analyzed the migration of markers in 32 consecutive patients with computed tomography scans postimplantation and at simulation. We implanted 147 markers (59 seeds, 88 coils) in or around 34 pulmonary tumors over 32 procedures, with one lesion implanted twice. Marker coordinates were rigidly aligned by minimizing fiducial registration error (FRE), the root mean square of the differences in marker locations for each tumor between scans. To also evaluate whether single markers were responsible for most migration, we aligned with and without the outlier causing the largest FRE increase per tumor. We applied the resultant transformation to all markers. We evaluated migration of individual markers and FRE of each group. Median scan interval was 8 days. Median individual marker migration was 1.28 mm (interquartile range [IQR] 0.78 − 2.63   mm ). Median lesion FRE was 1.56 mm ( IQR   0.92 − 2.95   mm ). Outlier identification yielded 1.03 mm median migration ( IQR   0.52 − 2.21   mm ) and 1.97 mm median FRE ( IQR   1.44 − 4.32   mm ). Outliers caused a mean and median shift in the centroid of 1.22 and 0.80 mm (95th percentile 2.52 mm). Seeds and coils had no statistically significant difference. Univariate analysis suggested no correlation of migration with the number of markers, contact with the chest wall, or time elapsed. Marker migration between implantation and simulation is limited and unlikely to cause geometric miss during tracking. PACS number: 87.57.N‐; 87.57.nm; 87.53.Ly